Properties of restrictions of the operator of multiplication by a continuous function - Shevchik, V.V. (Український математичний журнал, 1995)
Для оператора А множення на неперервну функцію a(t) в просторі L2[0,b]=H, дано опис двох множин нескінченновимірних підпросторів нескінченної корозмірності: I(A)={N⊂H:A/N — ізоморфізм }, K(A)={M⊂H:A/M — компактне відображення}. Як приклад розглянуто питання про безумовну базисність послідовності {a(t)en(t)},, де en(t) — ортонормована послідовність в L2[0,b]. For the operatorA of multiplication by a continuous functiona (t) in the Hilbert spaceL 2[0, b]=H, we give a description of two sets of infinite-dimensional subspaces with infinite codimensions:I(A)={N⊂H:A/N is an isomorphism},K(A)={M⊂H: A/M is a compact mapping}. As an application, we consider the problem of determining whether the sequence {a(t)en(t)}, where {en(t)} is an orthonormal basis in L2[0,b], is an unconditional basis.